Convergence as a System Basis for Building the Conception of the Security Management of Industrial Enterprise Development - Mushnykova Svitlana A. (Bìznes Inform, 2019)
The article is aimed at theoretical substantiation of the convergence process as a system basis for building the conception of the security management of industrial enterprise development. It is defined that the convergence in the economy is gaining its spread in the socio-economic relations in the post-industrial period. Researches by scholars are directed at several areas of the convergence process: convergence of economic models of countries; convergent-oriented development of regions and industries; convergent-oriented development of enterprise, and convergent approaches to enterprise management. It is substantiated that the convergence process is fundamental in forming the conception of the security management of industrial enterprise development through the «merging» of the structural components of «development» and «security» into a system of the conceptual bases. Studying the convergence results in defining the essence, purpose, specific and special principles, methods and techniques of managing the security of industrial enterprise development.